Peran Guru Penggerak pada Merdeka Belajar untuk Memperbaiki Mutu Pendidikan di Indonesia - Riowati, Riowati; Yoenanto, Nono H. (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this research is to provide an understanding that the concept of independent learning is in the form of a teacher driving program as an effort to improve the quality of education. The research method uses a literature review study of twenty articles from journals obtained from various sources. Data was collected by reviewing the official websites of Google Scholar, Research Gate, Sinta and Garuda. The search process was carried out by using keywords, quality of education, the concept of independent learning and driving teachers. Each article is selected based on specific questions compiled by the author as a first step. The research questions include; 1) What is the portrait of the quality of education; 2) What are the components that affect the quality of education; 3) How is the concept of implementing independent learning; 4) What is the role of the driving teacher. The results of the literature review study show that educational problems cannot be separated from the role of teachers as leaders. The ability of teachers as leaders in the concept of independent learning, namely the teacher acts as a motivator for fellow teachers in the school environment and motivates students. In conclusion, the portrait of education always experiences dynamics and changes. Various components of education influence each other to achieve quality education. Freedom to learn gives teachers the freedom to be creative in processing learning with students and the role of the driving teacher is very important as a leader in improving the quality of education in the future. Keywords: Motivating Teachers, Freedom to Learn, Quality of Education.